Penggunaan Aplikasi Plagiarism Checker dalam Pembelajaran Menulis Daring - Ponikem Ponikem (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2021)
The spread of Corona Virus Disease (Covid-19) which is widespread in almost all over the world requires the issuance of regulations governing the implementation of education in order to save the nation from the dangers of the Covid-19 pandemic. Studemts’ learning products need tobe verified, one of which is plagiarism check. As a best practice, checking plagiarism on writing products can be done more easily during online learning. Learning to write procedural texts with the theme